Antimicrobial Resistance in the 21st Century (Emerging Infectious Diseases of the 21st Century, 2018)
Antimicrobial resistance is now a general problem. Many of us have elderly relatives who died from a drug-resistant infection, and some of us have suffered from a resistant urinary infection that likely came from intestinal bacteria following antibiotic consumption. Antimicrobial Resistance in the 21st Century provides a broad introduction to the subject in which the situation with problematic pathogens is detailed, the biology of resistance is described, and gaining approval for new antibiotics is discussed. Some topics are immediately practical, such as watching for resistant pathogen sub-populations in cultures taken from patients; other topics point to future research efforts that may lead to new antimicrobials and ways to stimulate the action of existing ones. Overall, Antimicrobial Resistance in the 21st Century provides an update for physicians, serves as a starting point for graduate students interested in solving the resistance problem, and may serve as a text for a course on resistance. Lay readers familiar with microbiology will gain an appreciation for a medical issue that promises to be one of the most important of our time. Ignatius Fong, Department of Medicine, University of Toronto Series Editor - Emerging Infectious Diseases of the 21st Century David Shlaes, Founder, Anti-Infectives Consulting Editor - Antimicrobial Agents and Chemotherapy Karl Drlica, The Public Health Research Institute, New Jersey Medical School, Rutgers, The State University of New Jersey.